Co-creation of information leaflets to meet the support needs of people living with complex regional pain syndrome (CRPS) through innovative use of wiki technology. (2nd July 2016) - Rodham, Karen; Gavin, Jeff; Coulson, Neil; Watts, Leon
Abstract : Objective : People living with complex regional pain syndrome (CRPS) experience frustration with the lack of knowledge and understanding of CRPS as a pain condition. We report on our attempt to address this issue. Methods : People living with CRPS taking part in a larger study were invited to co-construct a CRPS wiki page that addressed the areas in which they had experienced the most difficulty. A blank wiki page was set up for participants to populate with issues they felt needed to be raised and addressed. Results : Participants failed to engage with the wiki technology. We modified our procedure and completed an inductive analysis of a sister-forum which participants were using as part of the larger study. Six issues of importance were identified. We used the discussion forum threads to populate the themes. Due to a continued lack of engagement with the wiki technology, the team decided to create a suite of leaflets which were piloted with delegates at a CRPS patient conference. Conclusions : Future work should be mindful of the extent to which patients are able and willing to share their experiences through such technology. Striking the balance between patient-endorsed and researcher-driven co-creation of such material is imperative.